Studi Meta Analisis Efek Penggunaan Media Digital Terhadap Keterampilan Berbahasa dan Kesantunan Siswa Sekolah Dasar - Muhayyarah, Muhayyarah; Firman, Firman; Guntur, Muhammad (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study discusses the influence of digital media use on language skills and language politeness among elementary school students. The study aims to determine the effect size of digital media use on these two aspects and to describe the pattern of effect variation based on previous research findings. This research uses a quantitative approach with a meta-analysis study design. Research data were obtained from 12 research reports that met the inclusion criteria and discussed the use of digital media in language learning for elementary school students. The effect size of each study was calculated and then analyzed using a random-effects model. A heterogeneity test was conducted to examine the variation of effects across studies. The results of the research indicate that the use of digital media has a positive and significant impact on language skills and language politeness of elementary school students. In addition, the synthesis results show diversity in effects across studies, which is influenced by differences in research context, types of digital media used, characteristics of the participants, and the learning approaches applied.